Saphenous neuropathy due to large hydatid cyst within long adductor muscle: case report and literature review - Ridvan Alimehmeti; Arsen Seferi; Arben Rroji; Mehdi Alimehmeti (Journal of Infection in Developing Countries)
An unusual case of saphenous neuropathy secondary to compression by a large hydatid cyst within the adductor longus muscle is reported. Solitary hydatid cyst(s) localized in the skeletal muscles occur rarely and often mimic soft tissue tumours. Presentation with signs of peripheral nerve compression by a hydatid cyst in an extremity is exceedingly rare. Diagnosis can be established by ultrasound, computerized tomography or magnetic resonance if clinically suspected. Clinical suspicion of hydatid origin of a solitary muscle cyst should be high especially in patients hailing from areas endemic for echinococcosis. Laboratory tests are usually unhelpful in such cases and needle biopsy carries the risk of anaphylactic shock and should therefore be avoided. Surgical removal of the unruptured cyst is the treatment of choice in cases of intramuscular hydatid cyst. In the present case, excision of the hydatid cyst was followed by complete clinical recovery. In the absence of systemic involvement, treatment with albendazole may be avoided.